Relation-inferred Self-efficacy: Investigations of Sources, Processes, and Interventions in Youth Sport - Saville, Paul (My University, 2014)
The purpose of this dissertation was twofold; the first purpose was to investigate the interpersonal sources of relation-inferred self-efficacy (RISE) and the metacognitive processes involved in self-efficacy development in youth sport. The second purpose was to translate those findings to recreational sport coaches. Study 1 explored the perceived sources of self-efficacy and identified a variety of relevant coaching behaviours sport participants used to formulate RISE. Findings showed a range of experiential as well as interpersonal factors were used to develop sport participants’ self-efficacy. In both contexts, participants described detailed examples of the verbal and nonverbal interactions they had with their coach that contributed to their RISE perceptions. Study 2 examined the relationships among coaching behaviour, RISE, and self-efficacy of boys and girls participating in youth sports and proceeded to investigate the causal processes involved in the interpretation of coaching behaviour. Results showed a positive relationship between coaches’ RISE-enhancing behaviour and athletes’ RISE perceptions; however, the association between coaching behaviour and self-efficacy differed by gender. Results were consistent with previous research in that sport participants’ RISE was shown to be strong and positively correlated with their self-efficacy beliefs. Overall, findings provided empirical support for RISE as a mediator of the coaching behaviour – self-efficacy relationship and provided initial evidence of a complementary pathway, outlined in Lent and Lopez (2002) model of relational efficacy beliefs that may be used to build self-efficacy among youth athletes. Study 3 examined the effects of a two-phase coach-athlete communication intervention on coaches’ perceptions toward integrating RISE-enhancing interactions into their coaching practice. Findings showed coaches’ knowledge, outcome expectations, and self-efficacy for implementing RISE-enhancing behaviours with their athletes improved significantly from pre-to post-intervention. Findings provided support for Bandura’s (1997) Self-efficacy Theory and emphasized the need to incorporate the learning preferences of youth sport coaches. The studies in this dissertation, advanced our understanding of the specific interpersonal sources that contribute to athletes’ RISE as well as the metacognitive processes involved in the development of children’s self-efficacy beliefs within a youth sport context. Taken together, findings of these studies suggest additional efforts to educate coaches on the potential they have to influence children’s RISE perceptions may be warranted.